Increasing the Efficiency of Heating Systems in Central and Eastern Europe and the Former Soviet Union - World Bank (Washington, DC, 2014)
This report examines the following questions: Which factors determine the choice of the economically preferred heating options from a set of alternatives? Under which circumstances is DH, decentralized heating with natural gas, or another alternative the preferred option? How does the institutional environment have to change in order to foster cost-effective heat supply and demand? How can the preferred option be implemented when the countries in Central and Eastern Europe and the former Soviet Union (CEE/FSU) are in a period of transition? To answer these questions, case studies of heat generation and delivery were carried out in 1996 in six CEE/FSU cities located in the Ukraine, Lithuania, Russia, Bulgaria, Romania, and Poland. In all six cities, DH is the dominant technology for supplying heat. This report summarizes the main findings from the case studies and provides details on the major issues encountered in modernizing DH systems, the commercialization of companies in the heating sector, and requirements for policy changes. It provides examples of best practices in the reform efforts in CEE/FSU and of investments designed to make heating more efficient.